2012
DOI: 10.1080/10291954.2012.11435166
|View full text |Cite
|
Sign up to set email alerts
|

Taxation students’ perceptions of open-book assessment prior to the qualifying examination of South African chartered accountants

Abstract: In this study taxation students' perceptions of open-book assessment, prior to their exposure to open-book assessment in the qualifying examination of South African chartered accountants, is explored. A focus group was conducted using the Interactive Qualitative Analysis methodology. In this focus group, taxation students without prior exposure to open-book assessment identified their perception themes (also referred to as affinities) on open-book assessment. These affinities were grouped together and describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…The earlier focus group study (Du Preez & Du Preez, 2012) identified a number of affinities, which can be defined as the themes generated in an IQA process by the focus group regarding perceptions of open-book assessment. Throughout the current article, brief references are made to this prior focus group study.…”
Section: Research Methodology and Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…The earlier focus group study (Du Preez & Du Preez, 2012) identified a number of affinities, which can be defined as the themes generated in an IQA process by the focus group regarding perceptions of open-book assessment. Throughout the current article, brief references are made to this prior focus group study.…”
Section: Research Methodology and Findingsmentioning
confidence: 99%
“…The classification of the affinities from the focus group study (Du Preez & Du Preez, 2012) is summarised as tentative SID assignments in Figure 1.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations